FeS-coated Fe / BC, preparation method thereof and application of FeS-coated Fe / BC in groundwater pollution remediation

FeS@Fe/BC material prepared by cross-linking and high-temperature pyrolysis of sodium alginate and Fe3+, the problem of pH dependence and low removal efficiency of nano-zero-valent iron in repairing groundwater pollution is solved, and the efficient removal of heavy metals and organics is achieved Pollutants and secondary pollution is avoided.

CN119158540APending Publication Date: 2024-12-20HAINAN HUANTAI ENVIRONMENTAL RESOURCES CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411291106.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing nano zero-valent iron repairs groundwater pollution and has problems such as pH dependence, easy agglomeration, oxidation and passivation. In the commonly used preparation methods, the reducing agent is expensive and produces secondary pollution, and lacks economical, green and efficient vulcanized nano zero-valent iron. Preparation method.

Method used

Alginic acid-Fe3+ gel with crosslinked sodium alginate and Fe3+ to form a three-dimensional network structure, nano zero-valent iron biochar (Fe@BC) was prepared by high-temperature pyrolysis, and vulcanized nano zero-valent iron was prepared in Na2S solution. Biochar (FeS@Fe/BC) to improve the performance of removing heavy metals and organic pollutants.

Benefits of technology

Under pH 6-8, the removal rates of Cr(VI), Pb2+, Cd2+, TCE and CTC by FeS@Fe/BC reached 99.5%, 99.1%, 98.7% and 99.8%, respectively, significantly improving zero-valent iron biology Carbon removal efficiency and reduce pH dependence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158540A_ABST
    Figure CN119158540A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of FeS-coated Fe / BC, the FeS-coated Fe / BC prepared by adopting the preparation method, and an application of the FeS-coated Fe / BC in groundwater pollution remediation. The method comprises the following steps: adding 0.5-2g / L of vulcanized nano zero-valent iron biochar functional material (FeS and Fe / BC) into to-be-repaired underground water with the pH value of 6-8, the Cr (VI) concentration of 0.5 mg / L, the Pb < 2 + > concentration of 0.5 mg / L, the Cd < 2 + > concentration of 0.05 mg / L, the carbon tetrachloride concentration of 250.0 mu g / L and the trichloroethylene concentration of 1050 mu g / L, and oscillating for 24 hours under the conditions of 25 DEG C and 110 r / min, so that the highest removal rates of Cr (VI), Pb < 2 + >, Cd < 2 + >, carbon tetrachloride and trichloroethylene are 99.5%, 99.1%, 98.7%, 99.8% and 99.7% respectively. According to the prepared FeS-coated Fe / BC, the TCE removal efficiency is improved by 18.9% compared with that of zero-valent iron biochar (BC-coated Fe) under the condition that the pH is 6. The FeS-coated Fe / BC has the characteristics of economy, greenness and high adaptability, and can be widely applied to groundwater pollution remediation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of groundwater remediation, and discloses a preparation method of FeS@Fe / BC, FeS@Fe / BC prepared by the preparation method, and application of the FeS@Fe / BC in groundwater pollution remediation. Background Art

[0002] Nano-zero-valent iron (nZVI) has the characteristics of strong adsorption capacity, high reducibility, and fast reaction rate. It is an environmental remediation medium that has received widespread attention and research. In recent years, a large number of studies have shown that nZVI can effectively remove a variety of heavy metal pollutants such as chromium, cadmium, and lead, and efficiently degrade organic pollutants such as trichloroethylene, chloroform, phenol, and toluene. However, there are still certain limitations in the remediation of environmental pollution by nZVI: such as pH dependence, easy agglomeration, oxidation and passivation, and poor electron selectivity. In addition, nZVI can easily react with water, oxygen or other ions to repair groundwater pollution, resulting in reduced removal capacity.

[0003] In order to improve the performance of nZVI in removing pollutants, the surface or structure of nZVI is usually modified by physical or chemical means. Sulfurization modification can effectively improve the performance of nZVI in removing pollutants and long-term reactivity.

[0004] Liquid-phase reduction one-step or two-step sulfurization is the main method for preparing S-nZVI. The commonly used reducing agent NaBH4 is not only expensive, but also forms a large amount of secondary pollutants during the reduction process. Developing an economical, green and efficient S-nZVI preparation method is a technical problem that needs to be solved urgently.

[0005] This patent uses sodium alginate as biomass, which is combined with Fe 3+ Cross-linking can form a three-dimensional network structure of alginate-Fe 3+ Nano-zero-valent iron biochar functional material (Fe@BC) was prepared by high-temperature pyrolysis, and Fe@BC was sulfided in Na2S solution to prepare sulfided nano-zero-valent iron biochar functional material (FeS@Fe / BC). Summary of the invention

[0006] In view of the above shortcomings, the present invention discloses a preparation method of a new material FeS@Fe / BC and a method for repairing Cr(VI), Pb 2+ 、Cd 2+ , TCE and CTC contaminated groundwater. Under the conditions of pH 6, 7, and 8, 0.5-2 g / L of FeS@Fe / BC was added. This method can detect the concentration of Cr(VI) at 0.5 mg / L, Pb 2+ The concentration is 0.5mg / L, Cd 2+The maximum removal rates of the three pollutants in the simulated contaminated groundwater with a concentration of 0.05 mg / L, carbon tetrachloride (CTC) concentration of 250.0 μg / L, and trichloroethylene (TCE) concentration of 1050 μg / L were 99.5%, 99.1%, 98.7%, 99.8%, and 99.7%, respectively.

[0007] The present invention is achieved by the following technical means:

[0008] The present invention first discloses a method for preparing FeS@Fe / BC, comprising:

[0009] (1) adding the biomass solution to the metal solution, standing for 24 hours and then washing with deionized water to obtain a biomass-metal gel for use;

[0010] (2) The biomass-metal gel is vacuum dried and then oven dried to obtain a dry gel;

[0011] (3) placing the dried gel in a tubular furnace, evacuating the furnace, heating to 900°C under nitrogen protection, and pyrolyzing at a constant temperature for 3 h. After the pyrolysis is completed, the temperature is lowered to room temperature to obtain BC@Fe;

[0012] (4) BC@Fe was placed in a Na2S solution and shaken at 25°C and 120 r / min for 2 h. After filtration, it was vacuum dried at 50°C to obtain FeS@Fe / BC.

[0013] Furthermore, the biomass solution in step (1) is prepared by the following method:

[0014] Dissolve 30 g of biomass in 1 L of deionized water until fully dissolved to obtain a sodium alginate solution;

[0015] The metal solution in step (1) is prepared by the following method:

[0016] 3L of metal solution was prepared with deionized water, and the FeCl3 concentration in the metal solution was 0.3mol / L.

[0017] Furthermore, the biomass includes but is not limited to sodium alginate, brown algae oligosaccharide, and chitosan.

[0018] Furthermore, the biomass is sodium alginate.

[0019] Furthermore, in step (2), the vacuum drying temperature is 60° C., the drying temperature is 100° C., and the drying time is 3 h.

[0020] Furthermore, in step (3), the nitrogen flow rate is 100 mL / min, the temperature is increased to 200°C at a heating rate of 5°C / min, and then the temperature is increased to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the mixture is cooled at a cooling rate of 10°C / min.

[0021] Furthermore, in step (4), the amount of BC@Fe added is 1 g, the amount of Na2S·9H2O added is 2.6 g, and the amount of deionized water is 50 mL.

[0022] The present invention also discloses FeS@Fe / BC prepared according to any of the above preparation methods.

[0023] The present invention also discloses a method for remediating groundwater pollution using the FeS@Fe / BC, comprising:

[0024] FeS@Fe / BC was added to the groundwater to be remediated and remediation was carried out at room temperature.

[0025] Furthermore, the dosage of the FeS@Fe / BC is 0.5-2 g / L.

[0026] Furthermore, the concentration of Cr(VI) in the groundwater to be repaired is 0.5 mg / L, and the concentration of Pb 2+ The concentration is 0.5mg / L, Cd 2 + The concentration is 0.05 mg / L, the concentration of carbon tetrachloride (CTC) is 250.0 μg / L, and the concentration of trichloroethylene (TCE) is 1050 μg / L;

[0027] The pH value of the groundwater to be repaired is 6-8, the repair temperature is 20-35°C, and the repair time is 24-48 hours.

[0028] The beneficial effects of the present invention are:

[0029] 1. Compared with zero-valent iron biochar, the FeS@Fe / BC prepared by the present invention has an improved removal efficiency of Cr(VI) by 26.6% under pH 2 and an improved removal efficiency of TCE by 18.9% under pH 6.

[0030] 2. Add 0.2g FeS@Fe / BC to pH 6, Cr(VI) concentration is 0.5mg / L, Pb 2+ The mass concentration is 0.5mg / L, Cd 2+The simulated groundwater with a mass concentration of 0.05 mg / L, a mass concentration of carbon tetrachloride (CTC) of 250.0 μg / L, and a mass concentration of trichloroethylene (TCE) of 1050 μg / L was shaken at 25 °C and 110 r / min for 24 h. 2+ 、Cd 2+ The maximum removal rates of carbon tetrachloride (CTC) and trichloroethylene (TCE) are 99.5%, 99.1%, 98.7%, 99.8% and 99.7%, respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the XRD pattern of FeS@Fe / BC prepared in Example 1 of the present invention;

[0032] Figure 2 Fe 2p (a) and S2p (b) spectra of FeS@Fe / BC prepared in Example 1 of the present invention;

[0033] Figure 3 This is a comparison chart of the Cr(VI) adsorption performance of Fe@BC, FeS@Fe / BC-1, FeS@Fe / BC, FeS@Fe / BC-3, and FeS@Fe / BC-4.

[0034] Figure 4 This is a comparison chart of TCE removal performance of Fe@BC and FeS@Fe / BC.

[0035] Figure 5 Experimental diagram of FeS@Fe / BC remediation of groundwater pollution. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0037] Example 1

[0038] Take 30 g of sodium alginate (SA) and add it into 1 L of deionized water to dissolve it. Stir it thoroughly with an electric stirrer to obtain a sodium alginate solution.

[0039] Prepare 3L FeCl3 solution with deionized water, the FeCl3 concentration is 0.3mol / L;

[0040] Sodium alginate was dropped into FeCl3 solution, allowed to stand for 24 h, and then washed with deionized water to prepare alginate-Fe 3+ gel;

[0041] Alginate-Fe 3+ The gel was placed in a vacuum drying oven and dried at 60 °C under vacuum conditions, and then dried at 100 °C for 3 h;

[0042] The dried gel was placed in a tubular furnace, evacuated, and nitrogen was introduced at a nitrogen flow rate of 100 mL / min. The temperature was raised to 200°C at a heating rate of 5°C / min, and then raised to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the gel was cooled at a rate of 10°C / min. When the temperature in the tube dropped to room temperature, the material was taken out to obtain Fe@BC.

[0043] 1 g of Fe@BC was added to 50 mL of Na2S·9H2O (2.6 g) solution, shaken at 25°C and 120 r / min for 2 h, filtered and dried in vacuum at 50°C to obtain FeS@Fe / BC.

[0044] The XRD pattern of FeS@Fe / BC prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the three strong characteristic diffraction peaks are located at 2θ = 44.67°, 65.02° and 82.3°, which are consistent with Fe 0 The diffraction peaks are consistent with the standard card (PDF#06-0696), corresponding to the (110), (200) and (211) crystal planes of Fe respectively; one weaker diffraction peak is located at 2θ=41.85°, which is consistent with the FeS standard card (PDF#65-3356), corresponding to the (203) crystal plane of FeS; one weaker diffraction peak is located at 2θ=60.9°, which is consistent with the FeS2 standard card (PDF#65-2567), corresponding to the (112) crystal plane of FeS2.

[0045] The XPS image of FeS@Fe / BC is shown in Figure 2 The XPS analysis of Fe element of FeS@Fe / BC is shown in Figure 2 a: Fe 2p 3 / 2 The absorption peak can be fitted into two peaks, Fe 2p 1 / 2 The absorption peak can be fitted into three peaks. The peak area of ​​the fitted peak at 718.5 eV accounts for 15.6% of the total peak area, which is Fe 0 The peak area of ​​the fitting peaks at 710.90 and 724.70 eV accounts for 53% of the total peak area, which is the absorption peak of Fe(Ⅱ), and the peak area of ​​the fitting peaks at 712.90 and 729.2 eV accounts for 31.4% of the total peak area, which is the absorption peak of Fe(Ⅲ). The XPS analysis of the S element of FeS@Fe / BC is shown in Figure 2As shown in Figure 2b, the S2p absorption peak can be fitted into three peaks. The peak area of ​​the fitted peak at 163.7 eV accounts for 49.6% of the total peak area, which is S 2- The peak area of ​​the fitting peak at 164.9 eV accounts for 24.5% of the total peak area, which is S2 2- The absorption peak at 168.4 eV accounts for 25.9% of the total peak area, which is SO4 2- absorption peak.

[0046] Comparative Example 1

[0047] Compared with Example 1, the amount of Na2S·9H2O was changed from 2.6 g to 7.2 g, as follows:

[0048] Take 30 g of sodium alginate (SA) and add it into 1 L of deionized water to dissolve it. Stir it thoroughly with an electric stirrer to obtain a sodium alginate solution.

[0049] Prepare 3L FeCl3 solution with deionized water, the FeCl3 concentration is 0.3mol / L;

[0050] Sodium alginate was dropped into FeCl3 solution, allowed to stand for 24 h, and then washed with deionized water to prepare alginate-Fe 3+ gel;

[0051] Alginate-Fe 3+ The gel was placed in a vacuum drying oven and dried at 60 °C under vacuum conditions, and then dried at 100 °C for 3 h;

[0052] The dried gel was placed in a tubular furnace, evacuated, and nitrogen was introduced at a nitrogen flow rate of 100 mL / min. The temperature was raised to 200°C at a heating rate of 5°C / min, and then raised to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the gel was cooled at a rate of 10°C / min. When the temperature in the tube dropped to room temperature, the material was taken out to obtain Fe@BC.

[0053] 1 g BC@Fe was added to 50 mL of Na2S·9H2O (7.2 g) solution, shaken at 25°C and 120 r / min for 2 h, and then filtered and dried in vacuum at 50°C to obtain FeS@Fe / BC-1.

[0054] Comparative Example 2

[0055] Compared with Example 1, the amount of Na2S·9H2O was changed from 2.6 g to 0.5 g, as follows:

[0056] Take 30 g of sodium alginate (SA) and add it into 1 L of deionized water to dissolve it. Stir it thoroughly with an electric stirrer to obtain a sodium alginate solution.

[0057] Prepare 3L FeCl3 solution with deionized water, the FeCl3 concentration is 0.3mol / L;

[0058] Sodium alginate was dropped into FeCl3 solution, allowed to stand for 24 h, and then washed with deionized water to prepare alginate-Fe 3+ gel;

[0059] Alginate-Fe 3+ The gel was placed in a vacuum drying oven and dried at 60 °C under vacuum conditions, and then dried at 100 °C for 3 h;

[0060] The dried gel was placed in a tubular furnace, evacuated, and nitrogen was introduced at a nitrogen flow rate of 100 mL / min. The temperature was raised to 200°C at a heating rate of 5°C / min, and then raised to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the gel was cooled at a rate of 10°C / min. When the temperature in the tube dropped to room temperature, the material was taken out to obtain Fe@BC.

[0061] 1 g BC@Fe was added to 50 mL of Na2S·9H2O (0.5 g) solution, shaken at 25°C and 120 r / min for 2 h, and then filtered and dried in vacuum at 50°C to obtain FeS@Fe / BC-3.

[0062] Comparative Example 3

[0063] Compared with Example 1, the amount of Na2S·9H2O was changed from 2.6 g to 0.25 g, as follows:

[0064] Take 30 g of sodium alginate (SA) and add it into 1 L of deionized water to dissolve it. Stir it thoroughly with an electric stirrer to obtain a sodium alginate solution.

[0065] Prepare 3L FeCl3 solution with deionized water, the FeCl3 concentration is 0.3mol / L;

[0066] Sodium alginate was dropped into FeCl3 solution, allowed to stand for 24 h, and then washed with deionized water to prepare alginate-Fe 3+ gel;

[0067] Alginate-Fe 3+ The gel was placed in a vacuum drying oven and dried at 60 °C under vacuum conditions, and then dried at 100 °C for 3 h;

[0068] The dried gel was placed in a tubular furnace, evacuated, and nitrogen was introduced at a nitrogen flow rate of 100 mL / min. The temperature was raised to 200°C at a heating rate of 5°C / min, and then raised to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the gel was cooled at a rate of 10°C / min. When the temperature in the tube dropped to room temperature, the material was taken out to obtain Fe@BC.

[0069] 1 g BC@Fe was added to 50 mL of Na2S·9H2O (0.25 g) solution, shaken at 25°C and 120 r / min for 2 h, filtered and dried in vacuum at 50°C to obtain FeS@Fe / BC-4.

[0070] Test Example 1

[0071] The materials obtained in Example 1 and Comparative Examples 1 to 3 were removed Cr(VI) Performance Comparison

[0072] Weigh 0.015g of prepared Fe@BC, FeS@Fe / BC-1, FeS@Fe / BC, FeS@Fe / BC-3, and FeS@Fe / BC-4 and add pH=2, 100mL, and 50mg / L Cr(Ⅵ) The conical flask was placed in a shaker for 24 hours and then taken out. The upper layer of solution was diluted and tested with a UV-visible spectrophotometer. Cr(Ⅵ) Concentration. Three parallel experiments were performed in each series.

[0073] The adsorption capacity of FeS@Fe / BC-1, FeS@Fe / BC, FeS@Fe / BC-3 and FeS@Fe / BC-4 on Cr(VI) in solution is shown in Figure 2. Figure 3 It can be observed that the removal rate of Cr(VI) by FeS@Fe / BC is the highest at 97.4%, the removal rate of Cr(VI) by FeS@Fe / BC-4 is the lowest at 43.5%, the removal rate of Cr(VI) by FeS@Fe / BC-3 is 49.2%, the removal rate of Cr(VI) by FeS@Fe / BC-1 is 84.9%, and the removal rate of Cr(VI) by BC@Fe is 70.8%.

[0074] Test Example 2

[0075] TCE removal experiment

[0076] The preparation concentration is 20 mg·L -1 TCE aqueous solution, stabilizer is 1% ethanol and 1% tert-butanol, adjust the solution pH to 6. Take 15mL of the reaction solution and add it to a brown cillin bottle, add 0.05g BC@Fe and FeS@Fe / BC respectively, shake on a shaker for 30min, filter the mixed solution after the reaction is completed, take 2mL of the filtrate and add it to a 5mL centrifuge tube, add 2mL of n-hexane, shake at room temperature for 5min, let it stand for 10min, take 1mL of the upper organic phase to a 2mL gas phase bottle, and then use a high-performance gas chromatograph to test the residual TCE concentration. Each group of experiments was repeated 3 times.

[0077] Comparison of TCE removal ability of BC@Fe and FeS@Fe / BC in solution Figure 4 As shown, it can be observed that the removal efficiency of TCE by FeS@Fe / BC is 98.2% and that by BC@Fe is 79.3%.

[0078] Test Example 3

[0079] Groundwater remediation experiment

[0080] China's groundwater quality standard (GB / T 14848-2017) stipulates: Class V groundwater pollutants Cr(VI), Pb 2+ 、Cd 2+ The mass concentration requirements for CTC and TCE are Cr(VI) less than 0.10 mg / L, Pb 2+ Less than 0.10mg / L, Cd 2+ A mixed solution with a concentration of less than 0.01 mg / L, carbon tetrachloride (CTC) less than 50.0 μg / L, and trichloroethylene (TCE) less than 210 μg / L. Prepare 5 times the concentration of Class V groundwater (Cr(VI), Pb 2+ 、Cd 2+ , CTC, TCE) as simulated sewage. Adjust the pH of simulated sewage to 6, take 100mL of simulated sewage, add 0.05g, 0.1g, and 0.2g of FeS@Fe / BC materials to conical flasks, and shake at 25℃ and 110r / min for 24h. After removal, test Cr(VI), Pb 2+ 、Cd 2+ , CTC, TCE residual concentration. Carry out 3 sets of parallel experiments and take the average value of the results. Adjust the simulated sewage pH to 7 and 8 and repeat the above experiments.

[0081] Under the conditions of groundwater pH 6, 7, and 8, the remediation effect of FeS@Fe / BC on groundwater is as follows: Figure 5 As shown. Adding 0.2g of material to groundwater with pH 6, the Cr(VI) and Pb 2+ 、Cd 2+ The removal rates of carbon tetrachloride (CTC) and trichloroethylene (TCE) are 99.5%, 98.9%, 98.7%, 99.6% and 99.7% respectively.

[0082] Add 0.2g of the material to groundwater at pH 7, and the Cr(VI), Pb 2+ 、Cd 2+ The removal rates of carbon tetrachloride (CTC) and trichloroethylene (TCE) are 98.1%, 99.1%, 98.2%, 99% and 99.3% respectively.

[0083] Add 0.2g of material to groundwater with pH 8, and the Cr(VI), Pb 2+、Cd 2+ The removal rates of carbon tetrachloride (CTC) and trichloroethylene (TCE) are 98.5%, 98.8%, 98%, 99.8% and 99.6% respectively.

[0084] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing FeS@Fe / BC, include: (1) adding the biomass solution to the metal solution, standing for 24 hours and then washing with deionized water to obtain a biomass-metal gel for use; (2) The biomass-metal gel is vacuum dried and then oven dried to obtain a dry gel; (3) placing the dried gel in a tubular furnace, evacuating the furnace, heating to 900°C under nitrogen protection, and pyrolyzing at a constant temperature for 3 h. After the pyrolysis, the temperature was cooled to room temperature to obtain BC@Fe; (4) Place BC@Fe in Na 2 The solution was shaken at 25 °C and 120 r / min for 2 h, filtered and dried at 50 °C in vacuum to obtain FeS@Fe / BC.

2. The preparation method according to claim 1, in: The biomass solution in step (1) is prepared by the following method: Dissolve 30 g of biomass in 1 L of deionized water until fully dissolved to obtain a biomass solution; The metal solution in step (1) is prepared by the following method: Prepare 3L of metal solution with deionized water. The metal solution contains FeCl 3 The concentration is 0.3mol / L.

3. The preparation method according to claim 1, in: The vacuum drying temperature in step (2) is 60° C., the drying temperature is 100° C., and the drying time is 3 h.

4. The preparation method according to claim 1, in: The nitrogen flow rate of step (3) is 100 mL / min, the temperature is increased to 200°C at a heating rate of 5°C / min, and then the temperature is increased to 900°C at a heating rate of 10°C / min. After constant temperature pyrolysis at 900°C for 3 hours, the mixture is cooled at a cooling rate of 10°C / min.

5. The preparation method according to claim 1, in: Step (4) The amount of BC@Fe added is 1g, Na 2 S·9H 2 The amount of O added was 2.6 g.

6. FeS@Fe / BC prepared according to any one of the preparation methods of claims 1 to 5.

7. A method for remediating groundwater pollution using the FeS@Fe / BC described in claim 6, include: FeS@Fe / BC was added to the groundwater to be remediated and remediation was carried out at room temperature.

8. The repair method according to claim 7, in: The dosage of the FeS@Fe / BC is 0.5-2 g / L.

9. The repair method according to claim 7, in: The concentration of Cr(VI) in the groundwater to be repaired is 0.5 mg / L, and the concentration of Pb 2+ The concentration is 0.5mg / L, Cd 2+ The concentration is 0.05 mg / L, the concentration of carbon tetrachloride is 250.0 μg / L, and the concentration of trichloroethylene is 1050 μg / L; The pH value of the groundwater to be repaired is 6-8, the repair temperature is 20-35°C, and the repair time is 24-48 hours.

Citation Information

Cited By

  • Method for preparing FeS / FeSn carbon aerogel and repairing hexavalent chromium contaminated soil

    CN120648463A

  • A FeS / FeS n Preparation of carbon aerogels and methods for remediation of hexavalent chromium contaminated soil

    CN120648463B